The political-pedagogical project in three basic education schools in Ponta Grossa, Brazil: limits and potentialities - Barche Alves, Murilo (2025)
This article, derived from research conducted over the years 2021 and 2022, examines the contradictions between theory and practice regarding the political-pedagogical project, a fundamental document that guides schools in Brazil. The qualitative and exploratory research was carried out as part of a Master's in Education and focused on three primary schools located in Ponta Grossa, in the state of Paraná. The main objective was to analyze the potential of the political-pedagogical project as a tool for democratic management, the implementation of school autonomy, and its role in social transformation. To achieve this, data was collected through documentary research and semi-structured interviews with members of the school administration, teachers, and students from each school. The data analysis methodology was based on historical-dialectical materialism, with an emphasis on the dialectical categories of alienation, contradiction and work. The study also aims to contextualize education within the capitalist society, emphasizing the intrinsic relationship between education and politics. The political-pedagogical project fits into this scenario, with the proposal for unification and collective participation. However, the analyzed data reveal a significant discrepancy between theory and practice in the investigated schools. It was observed that the document, in many cases, assumes a bureaucratic function, without ensuring the effective participation of all school stakeholders, particularly students. The research concludes that, although the political-pedagogical project holds great potential for promoting transformative educational practices, it is necessary to ensure the active participation of all involved, overcoming alienation and the contradictions that still permeate the current educational system.